1995
DOI: 10.1128/aac.39.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary pharmacokinetics of clarithromycin and of erythromycin

Abstract: The intrapulmonary pharmacokinetics of orally administered clarithromycin (500 mg every 12 h for five doses) or erythromycin (250 mg every 6 h for nine doses) were studied in 32 healthy adult volunteers. Four of the subjects, two in the clarithromycin group and two in the erythromycin group, were smokers. Bronchoscopy, bronchoalveolar lavage, and venipuncture were performed at 4, 8, 12, 24, and 48 h after administration of the last dose of clarithromycin and at 4, 8, and 12 h after administration of the last d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
76
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 32 publications
12
76
0
Order By: Relevance
“…The urea concentration in BALF was first corrected for possible contamination with urea from blood using the method described previously 64 65 The concentration of ALX-0171 in epithelial lining fluid was calculated as described in different studies 64-67 using the following formula: ELF [ALX-0171] = BALF [ALX-0171] X ([Urea Plasma ]/[Urea BALF Corr ]). Where: ELF [ALX-0171] is the ALX-0171 concentration in epithelial lining fluid, BALF [ALX-0171] is the ALX-0171 concentration in recovered BALF, [Urea Plasma ] is the concentration of urea in plasma and [Urea BALF Corr ] is the corrected urea concentration in BALF.…”
Section: Methodsmentioning
confidence: 99%
“…The urea concentration in BALF was first corrected for possible contamination with urea from blood using the method described previously 64 65 The concentration of ALX-0171 in epithelial lining fluid was calculated as described in different studies 64-67 using the following formula: ELF [ALX-0171] = BALF [ALX-0171] X ([Urea Plasma ]/[Urea BALF Corr ]). Where: ELF [ALX-0171] is the ALX-0171 concentration in epithelial lining fluid, BALF [ALX-0171] is the ALX-0171 concentration in recovered BALF, [Urea Plasma ] is the concentration of urea in plasma and [Urea BALF Corr ] is the corrected urea concentration in BALF.…”
Section: Methodsmentioning
confidence: 99%
“…Standardized bronchoscopy and bronchoalveolar lavage (BAL) (8)(9)(10)(11)(12)(13) were performed in the Clinical Trials Center at 4, 8, 12, 24, or 48 h after the administration of the last dose. Blood pressure, heart rate, respiratory rate, and temperature were recorded prior to, and at the completion of, bronchoscopy and as clinically indicated following the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers (1)(2)(3)(4)(5)(8)(9)(10)(11)(12)(13) have developed techniques for the measurement, in vivo, of the concentrations of drugs in ELF and AC. The purpose of this study was to determine the steady-state intrapulmonary concentrations and intrapulmonary pharmacokinetic parameters of orally administered linezolid in healthy volunteers.…”
mentioning
confidence: 99%
“…Despite high MIC values, some bronchopulmonary pharmacokinetic studies demonstrated that high concentrations of CLR were achieved in alveolar macrophages and epithelial lining fluid (ELF), with high ratios of concentrations in ELF and alveolar macrophages compared with that in plasma assessed in healthy volunteers [74][75][76]. These results suggest that high concentrations of CLR are achieved in ELF and alveolar macrophage cells, which exceed the in vitro MIC values by several fold.…”
Section: Discussionmentioning
confidence: 76%